Influência do exercício físico e da N-acetilcisteína no remodelamento cardíaco e estresse oxidativo de ratos com sobrecarga pressórica crônica - Abreu Reyes, David Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Objective. To evaluate the effects of N-acetylcysteine (NAC) on cardiac remodeling in rats during transition from compensated left ventricular (LV) hypertrophy to heart failure. Methods and Results. Four months after inducing aortic stenosis (AS), Wistar rats were assigned into three groups: Sham, AS, and AS treated with NAC (AS-NAC for eight weeks). NAC restored myocardial total glutathione (Sham 20.8±3.00; AS 12.6±2.92; AS-NAC 17.6±2.45 nmol/g tissue; p<0.05 AS vs Sham and AS-NAC). Malondialdehyde serum concentration was lower in AS-NAC and myocardial lipid hydroperoxide was higher in AS (Sham 199±48.1; AS 301±36.0; AS-NAC 181±41.3 nmol/g tissue). Glutathione peroxidase activity was lower in AS than Sham. Echocardiogram showed LV concentric hypertrophy and dysfunction before and after treatment. Tissue Doppler imaging (TDI) of mitral annulus systolic velocity and isovolumetric relaxation time were lower in AS than Sham; in AS-NAC these parameters were between those in Sham and AS and did not differ from either group. NAC reduced p-ERK and p-JNK protein expression, attenuated myocyte hypertrophy and myocardial fibrosis, and decreased lung congestion frequency. Conclusion. N-acetylcysteine restores myocardial total glutathione, reduces oxidative stress, improves MAPK signaling, and attenuates myocyte hypertrophy, myocardial fibrosis, and LV dysfunction in aortic stenosis rats.
N-acetylcysteine influence on oxidative stress and cardiac remodeling in rats during transition from compensated left ventricular hypertrophy to heart failure
Keywords: Exercício físico; Insuficiência cardíaca; N-Acetilcisteína; Ventrículo izquierdo